Lexis and Grammar of Mitochondrial RNA Processing in Trypanosomes. Issue 4 (April 2020) - Aphasizheva, Inna; Alfonzo, Juan; Carnes, Jason; Cestari, Igor; Cruz-Reyes, Jorge; Göringer, H. Ulrich; Hajduk, Stephen; Lukeš, Julius; Madison-Antenucci, Susan; Maslov, Dmitri A.; McDermott, Suzanne M.; Ochsenreiter, Torsten; et al.
Abstract : Trypanosoma brucei spp. cause African human and animal trypanosomiasis, a burden on health and economy in Africa. These hemoflagellates are distinguished by a kinetoplast nucleoid containing mitochondrial DNAs of two kinds: maxicircles encoding ribosomal RNAs (rRNAs) and proteins and minicircles bearing guide RNAs (gRNAs) for mRNA editing. All RNAs are produced by a phage-type RNA polymerase as 3′ extended precursors, which undergo exonucleolytic trimming. Most pre-mRNAs proceed through 3′ adenylation, uridine insertion/deletion editing, and 3′ A/U-tailing. The rRNAs and gRNAs are 3′ uridylated. Historically, RNA editing has attracted major research effort, and recently essential pre- and postediting processing events have been discovered. Here, we classify the key players that transform primary transcripts into mature molecules and regulate their function and turnover. Highlights: Mitochondrial RNA processing events in kinetoplastid protists include 5′ modification, 3′–5′ degradation, internal sequence changes by U-insertion/deletion mRNA editing, and nontemplated 3′ extensions. The specificity of mRNA editing is dictated by gRNAs while 5′ modifications and 3′ extensions are controlled by diverse pentatricopeptide repeat (PPR) RNA-binding factors. Antisense transcription plays a central role in delimiting 3′ termini of mature RNAs. Macromolecular protein and ribonucleoprotein (RNP) complexes and auxiliary factors involved in these processes have been identified and characterized to varying degrees. This review discusses recent developments and introduces a consensus nomenclature for mitochondrial RNA-processing complexes and factors in Trypanosoma brucei .